PRODUTIVIDADE DE CULTIVARES DE PANICUM MAXIMUM NO NOROESTE DO RIO GRANDE DO SUL: ANO DE ESTABELECIMENTO - Writzl, Adalberto C.; Maixner, Adriano R.; Sartori, Cesar O.; Uhde, Leonir T.; Fernandes, Sandra B. V.; Jezewski, Tiago J. (Salão do Conhecimento, 2013)
Resumo